Systemic blood flow relations in conscious South American rattlesnakes - Filogonio, Renato [UNESP]; Taylor, Edwin W. [UNESP]; Carreira, Laura B. T. [UNESP]; Leite, Gabrielle S. P. C.; Abe, Augusto S. [UNESP]; Leite, Cleo A. C. (Soc Brasileira Herpetologia, 2014)
Estimating total systemic blood flow based on measurements from a single aortic arch is common practice in cardiovascular studies on reptiles to avoid heavy instrumentation and consequent stress responses. This practice requires the validation of a specific correction factor that expresses the relationship between the measured blood flow and the blood flow to be estimated. Misleading estimations may occur when correction factors are used in different conditions from those they were originally measured. Despite recognized as a problem, such misleading estimations are common in physiology. In the present study, we derived values for correction factors to estimate systemic blood flow in the South American rattlesnake, Crotalus durissus, following recovery from anesthesia, using serial measurements of blood flow in the three main systemic arteries, left or distal right aortic arches and the carotid artery. Blood flow recorded in the left aortic arch provided the most reliable and less variable correction factors. Different from previously published, blood flow distribution in the systemic circulation varied with temperature. We suggest the use of the specific correction factors present in this paper for different experimental protocols and temperatures. Furthermore, we can affirm that unilateral left vagotomy, which effectively ablated control of right-left shunts, does not affect systemic blood flow distribution, so the same correction factors can be used.
Keywords: Anaesthesia; Blood flow; Cardiovascular system; Correction factor; Crotalinae; Crotalus durissus; Vagotomy; Viperidae